NATRIUM CARBONATE (NA2CO3) AS INHIBITOR IN THE CORROSION PROTECTION ON STEEL PIPE ST 41 IN WATER PLUMBING ENVIRONMENTAL - I. G. A. Arwati; T. Izzati; Z. Arifin (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2016)
This study aimed to analyze the effect of adding to the rate of steel corrosion inhibitor and comparing the rate of corrosion on steel pipes with and without inhibitors. The testing conducted in Puspitek shown that the most optimum of the inhibitor contained with the addition of 1% due to changes of the pH from 7.30 to 11.80. This shows the increasing of pH occurred sizable value and followed by the declines of potential value (Ecorr) -700.53 mV to -512.39 mV. Thus, the decreasing occurred to the current corrosion value (Icorr) from 2.71 μA/cm2 to 0.31 μA/cm2, while the corrosion rate of carbon steel St 41 decreased most effective after adding 1% Na2CO3 as an inhibitor, the corrosion rate is changed from 1.2437 mpy to 0.1427 mpy.